150k views
4 votes
X²+2 √{3} xy-y²+2=0 Use a rotation of axes to eliminate the x y -term.

1 Answer

3 votes

Final answer:

To eliminate the xy-term in the equation x²+2 √{3} xy-y²+2=0, we can use a rotation of axes.

Step-by-step explanation:

To eliminate the xy-term in the equation x²+2 √{3} xy-y²+2=0, we can use a rotation of axes.

Let's define the angle of rotation as θ. By applying the rotation matrix, the new equation becomes:

x' = xcos(θ) - ysin(θ)
y' = xsin(θ) + ycos(θ)

By choosing the angle of rotation such that the xy-term is eliminated, we can find the new equation without the xy-term.

User Martin Doms
by
7.5k points